Impact of music-based interventions on subjective well-being: a meta-analysis of listening, training, and therapy in clinical and nonclinical populations - Zhang, Jie; Lu, Yanan; Mehdinezhadnouri, Katayoun; Liu, Junjie; Lu, Haohui (Frontiers in Psychology, 2025)
IntroductionThis meta-analysis aims to systematically evaluate the impacts of three types of Music-based interventions (MBIs)—music listening, music training, and music therapy on the subjective well-being (SWB) of clinical and non-clinical populations.MethodsThe study conducted a systematic search of Web of Science, PubMed, and Scopus (from inception to January 2025) using the PRISMA guidelines, and selected 10 studies with a total of 387 and 326 experimental and control groups, respectively. Study quality was assessed using the Cochrane Risk of Bias Tool for randomized controlled trials. A random-effects meta-analysis was then performed in Stata 18.0 to compute standardized mean differences (SMDs) and 95% confidence intervals (CIs).ResultsThe pooled effect sizes indicated that MBIs were significantly associated with higher levels of SWB compared with control conditions (SMD = 0.36, 95% CI: 0.06–0.65, p = 0.02). Subgroup analyses revealed significant variations across intervention types and populations. Music listening was significantly associated with higher SWB in clinical groups (SMD = 0.65, 95% CI: 0.02–1.29); however, no significant association was found in nonclinical groups (SMD = 0.28, 95% CI: −0.14–0.70), although a positive overall association was observed (SMD = 0.42, 95% CI: 0.06–0.77). Music training showed a significant positive association with SWB in clinical groups (SMD = 1.76, 95% CI: 1.04–2.48), but no significant association was found in nonclinical groups (SMD = −0.32, 95% CI: −0.84–0.20) or in the overall sample (SMD = 0.00, 95% CI: −0.77–0.78). In contrast, music therapy was significantly associated with improvements in SWB across both clinical and nonclinical populations.DiscussionThe results indicated that MBIs may improve SWB, though the strength of the association appears to vary depending on the type of intervention and the characteristics of the target population. Music training yielded the most significant effects in clinical populations, whereas music therapy was most effective in nonclinical populations. The effects of music training and music listening were less pronounced potentially due to differences in emotional needs, interactivity, and training difficulty. Future research should focus on individualized designs for intervention and further investigate the influence of factors such as type of intervention, duration, frequency, characteristics of participants, and reinforcement of interventions on the long-term effects on SWB.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42025641732.